Past of Philip Larkin’S Lost Empire: Exploring the Shifts in Philip Larkin's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Theearly work of an important writer always has a potential interest, since it islikely to contain anticipations of his later, finer poems. In Larkin’s case,however, this interest is limited because of the sharp break in his writingafter his first volume of poems. A sharp shift marked in the poetry of PhilipLarkin after The North Ship (1945).Larkin’s second volume, The LessDeceived, was published in 1955. By this time a full decade had passedsince the Second World War, and the poems of this volume were consequentlyinspired by the after-effects of the War. While the first phase of his poetrywas dominated by war-poetry, in the second phase, he focused his attention onthe glorious past and on socio-political conditions, a concern that was toprevail in the third and fourth phase of his poetry as well. Thirteen poems inthis volume also featured in XX Poems,which was published in 1951. Commenting on the poems of this volume,Larkin wrote in an unpublished letter, “They are a mixed bag.”